SAT0398 Spine immobilisation and neurological complications in vertebral osteomyelitis: results from a multicenter prospective study. (12th June 2018) - Bart, G.; Coiffier, G.; Merot, O.; Couderc, M.; Hoppe, E.; Cormier, G.; Ziza, J.-M.; Le Goff, B.
Abstract : Background: Neurological complications of vertebral osteomyelitis (VO) can be serious. In a previous work, 1 we showed that they occur in up to 40% of the patients. Bed rest and spine immobilisation by bracing is prescribed to decrease pain but also to prevent those complications. There is currently no consensus about the best immobilisation protocol to follow in VO. French guidelines recommend bracing for all patients whereas recently published American recommendations did not even mention spine immobilisation. Objectives: To describe the type and duration of prescription of spine immobilisation during VO. Methods: A prospective multicenter study was performed in 7 French centres. All patients with VO were followed prospectively: neurological complications, imaging findings, type and duration of immobilisation were reported. We present here the data of our study after 3 months of follow-up. Results: To date, 79 patients completed 3 months follow-up. Medium age was 67±15 years old with 66% of males. Median duration of symptoms before diagnosis was 27 days, IQR. 11–40 37 patients (47%) had staphylococcal infection. 35% of the patients had an abnormal neurological exam at baseline: 18 patients (23%) had minor neurological signs (sensory loss, radiculopathy or pyramidal syndrom), and 10 (12%) had major neurological signs (motor deficit or cauda equine syndrom). During hospital stay, 5 patient developed major neurological signs (median 5 days after diagnosis) and 7 minor neurological signs (median 6 days after diagnosis). Half of the patients with abnormal neurological exam at baseline had functional sequelae at 3 months. On MRI, 17% of patients had epidural phlegmon, 20% had anterior effacement of subarachnoidal space, and 16% had involvement of cervical spine. All these MRI signs were significantly associated with major neurological complications (p=0.004, p=0.004 and p=0.002, respectively). Median duration of bed rest was 9 days (IQR 7–18). Overall, only 60% of patients have been immobilised by bracing (90% of rigid bracing). Median duration of prescription was 8 weeks, IQR. 6–12 Patients who did not receive spine immobilisation had all a lumbar involvement, a normal neurological examination at baseline. None of them developed secondary neurological complications. They were no significant difference in age (72±16 versus 65±15 years old), sex or duration of the symptoms between patients who have been immobilised or not. Conclusions: Neurological complications occurred in 35% of our patients as published in previous VO cohort. Interestingly, 40% of our patients were not treated with bracing. They all had lumbar involvement and normal initial neurological examination. None of them developed secondary neurological complications. Bed rest without bracing might be the best therapeutic option for these patients, preventing the morbidity associated with bracing. Reference: [1] Bart, et al. Is There an Association Between Magnetic Resonance Imaging and Neurological Signs in Patients With Vertebral Osteomyelitis? A Retrospective Observational Study on 121 Patients. Medicine2016. Disclosure of Interest: None declared